Online Learning in Primary School during Covid-19 Pandemic: How Does It Look Like? - Hikmah, Annafi'atul; Wuryandani, Wuri; Zubaidah, Enny; Herwin, Herwin; Jhon, Winarni (LPPM Undiksha, 2021)
The Covid-19 pandemic has forced the learning system on schools to change drastically from face-to-face learning to online learning. Even though governments consider online learning as a solution to continue educational process, the sudden transformation from traditional learning into online learning has caused many challenges for teachers and students. Teachers did not have enough experience and knowledge about online learning such as online learning platforms and media. This was serious issue that needed to be solved since online learning platforms can help students and teachers to communicate and interact in online learning. This study aims to explore the online learning platform or media, challenges and strategies based on primary school teachers’ perspective. This research was a qualitative phenomenological design. This research conducted in-depth online interview towards 24 primary school teachers. Based on the result of interview, found that teachers applied varied online learning platform and media such as Whatsapp, Telegram, Google Classroom, Youtube Zoom, Google Meet, Microsoft Teams, Rumah Belajar, TVRI, and Google Form based on the consideration of its advantages, students condition and purpose of learning. However, teachers faced challenges regarding preparation, implementation, and assessment of online learning. Thus, teachers implemented varied strategies by improving their own skills and having good collaboration and communication with parents, students, and other peers.